2018
DOI: 10.1186/s12937-018-0331-4
|View full text |Cite
|
Sign up to set email alerts
|

High phosphorus intake and gut-related parameters – results of a randomized placebo-controlled human intervention study

Abstract: BackgroundIn recent years, high phosphate intakes were discussed critically. In the small intestine, a part of the ingested phosphate and calcium precipitates to amorphous calcium phosphate (ACP), which in turn can precipitate other intestinal substances, thus leading to a beneficial modulation of the intestinal environment. Therefore, we analysed faecal samples obtained from a human intervention study regarding gut-related parameters.MethodsSixty-two healthy subjects (men, n = 30; women, n = 32) completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…The genotoxicity and cytotoxicity of faecal water remained unchanged after supplementation with phosphate alone in one study [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The genotoxicity and cytotoxicity of faecal water remained unchanged after supplementation with phosphate alone in one study [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cats et al (1993) also showed that there was no change in the cytolytic activity of faecal water following calcium phosphate supplementation [ 28 ]. Trautvetter et al (2018) showed that there were no changes in the genotoxic potential or the cytotoxicity of faecal water following phosphate supplementation [ 13 ]. All these authors supposed that the formation of calcium phosphate complexes and the co-precipitation of bile acids or other intestinal substances may be responsible for a rather decreased toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 202 ] High Ca diets also impacted microbial fermentation, Ca phosphate increased proximal colon butyrate concentrations in rats, [ 203 ] while the supplementation of Ca carbonate within a human intervention trial significantly increased total fecal SCFA and acetate. [ 204 ]…”
Section: Mineralsmentioning
confidence: 99%